2016
DOI: 10.3109/09273948.2015.1125511
|View full text |Cite
|
Sign up to set email alerts
|

Retinoschisis in Pars Planitis

Abstract: Retinoschisis is a common complication in patients with PP. It is typically bilateral, and may develop or progress, despite control of uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Brockhurst [ 5 ] described that retinoschisis in chronic peripheral uveitis developed after several years of active disease, with massive exudation overlying the inferior portions of the ora serrata. Treatment of this form of retinoschisis was rarely necessary, with only one case needing wide scleral buckling with subsequent drainage of fluid due to progression [ 5 ]. Similarly, Pollack et al [ 4 ] reported that the schisis/ERD remained stable in 9 of 13 eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brockhurst [ 5 ] described that retinoschisis in chronic peripheral uveitis developed after several years of active disease, with massive exudation overlying the inferior portions of the ora serrata. Treatment of this form of retinoschisis was rarely necessary, with only one case needing wide scleral buckling with subsequent drainage of fluid due to progression [ 5 ]. Similarly, Pollack et al [ 4 ] reported that the schisis/ERD remained stable in 9 of 13 eyes.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that traction occurs due to contraction of snowbanking caused both tangential and radial traction on the pars plana and peripheral retina leading to peripheral retinal elevation. The elevation subsequently relieves further traction, explaining the lack of progression in the majority of cases [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonprogressive tractional elevations can be observed [125]. Progression of retinoschisis can be observed in active or inactive uveitis, but may require surgery to repair retinal detachment [126].…”
Section: Posterior Segmentmentioning
confidence: 99%